If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9rs + -3 = t Reorder the terms: -3 + 9rs = t Solving -3 + 9rs = t Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 9rs = 3 + t Combine like terms: -3 + 3 = 0 0 + 9rs = 3 + t 9rs = 3 + t Divide each side by '9s'. r = 0.3333333333s-1 + 0.1111111111s-1t Simplifying r = 0.3333333333s-1 + 0.1111111111s-1t
| 8x+12y=156 | | .7+1x=-.6 | | 36+7= | | 5n+2-7= | | 8(4x-2.5)=16 | | 4+-0.5y=x | | 3(1-x)=-(7x+5) | | 4(z+2)-7z=6(-0.5z+1)+2 | | 5(5c-1)-1=20c+4 | | 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) |